Tingkat Kecemasan sebagai Penghambat Kualitas Hidup Pasien dengan Hemodialisis di Rumah Sakit - MR, Merisdawati; Jamil, Mokhtar; Umifa, Kaslinda Nur (FORIKES, 2025)
Chronic kidney failure is an irreversible chronic disease that requires long-term care and hemodialysis, which can cause anxiety and affect the quality of life of patients. The purpose of this study was to analyze the relationship between anxiety levels and the quality of life of patients undergoing hemodialysis. This study was an observational analytical study with a cross-sectional design. The subjects involved in the study were 36 patients with chronic kidney failure undergoing hemodialysis. The patients were selected using a purposive sampling technique. The independent variable studied was the level of patient anxiety measured using the Hamilton Rating Scale for Anxiety (HRS-A). The dependent variable was the quality of life of patients measured using the World Health Organization Quality of Life Assessment (WHOQOL-BREF). Hypothesis testing was carried out using the Spearman-Rank correlation test. Based on the results of the analysis, the majority of patients experienced anxiety at a mild level (36.1%), while the most common quality of life was poor (86.1%). The p-value from the correlation test results was 0.004, so it was interpreted that there was a correlation between anxiety levels and the quality of life of patients. Furthermore, it was concluded that patient anxiety is an obstacle to the quality of patients with kidney failure undergoing hemodialysis.Keywords: chronic renal failure; hemodialysis; anxiety; quality of life ABSTRAK Gagal ginjal kronik merupakan penyakit kronis yang bersifat irreversible, yang membutuhkan perawatan jangka panjang dan hemodialisis, sehingga dapat mengakibatkan kecemasan dan berpengaruh terhadap kualitas hidup pasien. Tujuan penelitian ini adalah menganalisis hubungan antara tingkat kecemasan dengan kualitas hidup pasien yang menjalani hemodialisis. Penelitian ini merupakan studi analitik observasional, dengan rancangan cross-sectional. Subyek yang terlibat dalam penelitian adalah sejumlah 36 pasien dengan gagal ginjal kronik yang menjalani hemodialisis. Para pasien dipilih menggunakan teknik purposive sampling. Variabel bebas yang diteliti adalah tingkat kecemasan pasien yang diukur menggunakan Hamilton Rating Scale for Anxiety (HRS-A). Variabel terikat adalah kualitas hidup pasien yang diukur menggunakan World Health Organization Quality of Life Assessment (WHOQOL-BREF). Pengujian hipotesis dilakukan menggunakan uji korelasi Spearman-Rank. Berdasarkan hasil analisis, mayoritas pasien mengalami kecemasan pada level ringan (36,1%), sedangkan kualitas hidup terbanyak adalah buruk (86,1%). Nilai p dari hasil uji korelasi adalah 0,004, sehingga diinterpretasikan bahwa ada korelasi antara tingkat kecemasan dengan kualitas hidup pasien. Selanjutnya disimpulkan bahwa kecemasan pasien merupakan penghambat kualitas pasien dengan gagal ginjal yang menjalani hemodialisis.Kata kunci: gagal ginjal kronik; hemodialisis; kecemasan; kualitas hidup